Fish trader’s gender and niches in a declining coral reef fishery: implications for sustainability - Timothy R. McClanahan (Taylor & Francis Group, 2017)
Introduction: The state of natural resources is greatly influenced by market access. Consequently, resource trader’s incentives, decisions, and willingness to comply with management can influence efforts to achieve sustainability. Trader’s impacts will depend on their economic niches, which are influenced by cultural norms, skill, social relationships, profitability, and the spatial scale of markets. Consequently, we examined the potential of traders to influence fisheries’ sustainability by evaluating their jobs, gender roles, religion, socioeconomic status, association and perceptions of management systems, and future plans. We studied 142 traders in 19 Kenyan coral reef fisheries landing sites distributed among four gear management systems. Outcomes: We found a strong role of gender, geography, and religion in the participation of these fisheries that was primarily driven by fisheries’ profitability. The associations suggest that overfished fisheries should retain traders with low education, capital, and savings – often women; whereas sustainable stocks favor the opposite characteristics, and often men. Conclusions: Therefore, managing for increasing yields, profits, and sustainability could exclude women traders unless they successfully access or adopt the more traditional male economic niche. Gender coexistence is most likely to be achieved by managing for intermediate resource levels where net production, catch, and fish body size diversity are high. Further, reducing risk and increasing the capital and mobility of women traders should reduce their chances of exclusion when fisheries are sustainable.